To deny or to confess: An interrogation decision-making model - Yang, Yueran (2016)
This dissertation seeks to explain suspects’ decision-making processes within the context of a custodial interrogation by presenting a new model of confessions referred to as the interrogation decision-making model. The model proposes that suspects’ decision-making process can be analyzed at two different levels—a micro-level process and a macro-level process. Drawing on expected utility theory (Edwards, 1962; Shoemaker, 1982; Von Neumann & Morgenstern, 1944), the micro-level process of the model introduces a mathematical framework to explain the psychological mechanisms underlying suspects’ single interrogation decision at a certain point in time. The macro-level process of the model describes the dynamic nature of suspects’ multiple interrogation decisions throughout an interrogation. These two processes jointly explain suspects’ decisions to deny or confess guilt during a custodial interrogation. This dissertation also describes two experimental studies that tested key predictions generated by the model. Experiment 1 (N = 205) tested the prediction that suspects decide whether to deny or confess guilt on the basis of a proximal outcome’s perceived desirability, or in terms of the model, its perceived utility. Experiment 2 (N = 158) tested the prediction that suspects decide whether to deny or confess guilt on the basis of a distal outcome’s perceived utility. The results of the experiments were mixed. Whereas the utility of a proximal outcome did not significantly influence participants’ admissions and denials of prior misconduct, the utility of a distal outcome did. These findings provide partial support for the model by showing that a critical factor affecting suspects’ decision-making is the perceived utility of distal outcomes